Preservation of Intangible Ethnocultural Heritage in the Electronic Environment - E. D. Zhabko (Библиосфера)
The article considers the issues of preserving and updating the ethnocultural heritage of the peoples of the Russian Federation within the framework of the activities of museums, houses of folk art, higher educational institutions, academic research institutes. Institutions for which the preservation of cultural heritage is not the main essential activity, but has recently been actively developing, are characterized. These are federal and national universities and research institutes of the Russian academy of sciences. Universities integrate successfully knowledge related to intangible cultural heritage into educational programs. Research institutes have become reference bases in their regions in the study and preservation of national languages as objects of intangible cultural heritage, national literature and ethnography. The prospects for such activities of libraries are considered, a new role of which is given in the Federal Law N 402-FL “On the intangible ethnocultural property of the Russian Federation”. The possibility of digitizing and forming digital collections of objects of intangible cultural heritage recorded in the form of texts and static images in libraries, as well as information objects existing in the form of temporary representation (recording of musical works, dances, folklore) has been identified. Particular attention in digitization in libraries should be paid to funds on national languages, collections of audio recordings of folk music and ethnographic collections. Examples of the practice of presenting intangible ethnocultural heritage on federal and regional portals/sites are given.